Evaluating the Material Waste Reduction by Using Prefabrication in Building Construction in Kuala Lumpur - Nurul Aini, Osman; Lee, Na C.C. (2016)
Issues of construction waste are getting serious in the recent years. The generation of waste in the construction industry will soon affect the environmental issues. The rate of the wastage level is relatively high in Malaysia. The method of construction used in constructing a building is crucial as it can help to reduce the generation of material waste. In line with this, a study was carried out to analyse the types of material waste both in conventional and prefabrication method. Plus, an investigation for the level of material wastage between conventional and prefabrication method also been done. The scope of this study mainly focuses on the building contractor's firm registered under Construction Industry Development Board Malaysia (CIDB) in Kuala Lumpur area. The data were obtained and analysed by using frequency analysis, average index analysis and mean analysis. The results revealed that the average wastage reduction level was about 30% when the contractors implemented the prefabrication construction. This implies that an extensive use of prefabrication could considerably reduce construction waste generation in Kuala Lumpur.